Deterministic simulation and graphical representation of powered material handling vehicle movements to enhance pedestrian safety at the Ford Motor company. Issue 2 (2nd April 2020) - Higgins, M.; Ladbrook, J.; Khalwadekar, G.; Osman, M.
ABSTRACT: A deterministic Material Flow Analysis (MFA) simulation tool has been developed within Microsoft Excel allowing the user to simply and quickly enter relevant material and logistics data. This data is then processed mathematically stepping through time in user-specified intervals assessing stock levels and vehicle status. The monitoring of the material flow in this manner provides data resolution that has not been achievable within Ford prior to the use of simulation. A further extension was developed enabling effective communication of safety-critical simulation output to be presented diagrammatically as a "Material Flow Heat Map". Preliminary implementation has shown the tool is effective at both confirming expected and highlighting new, high-traffic hotspots in the plant. Through the development and implementation of these methods, the movement of vehicles is better understood allowing targeted engineering actions to improve productivity and enhance pedestrian safety for both existing and proposed future facilities.